Material Extrusion Additive Manufacturing of Lunar Soil Simulant Brick - Xun, Ailing; Chen, Yingyu; Zhang, Lu; Xu, Chao; Zou, Meng; Ren, Luquan (Journal of Progress in Civil Engineering, 2025)
In-situ utilization of lunar soil resources to create construction units such as bricks is one of the best methods for establishing architectures on the moon, avoiding the exorbitant costs associated with transporting materials and massive equipment from Earth. In the paper, bricks with grid structures made of lunar soil simulants are fabricated via direct ink writing (DIW), a material extrusion additive manufacturing technique. The lunar soil simulant ink is prepared by mixing lunar soil simulant powders with polylactic acid (PLA)/dichloromethane (DCM) binder in a volume ratio of 74:26 and then extruded from a nozzle with a diameter of 410μm to form cylindrical bricks following the preset printing path. The as-printed bricks are sintered under a vacuum condition at 1100 ℃ to enhance their mechanical properties. The sintered bricks exhibit dimensional shrinkages of around 10-15% due to PLA pyrolysis and sintering neck formation. Surprisingly, two of the sintered bricks display significantly greater mass loss ratios than the others, which may be due to gas generation from certain minerals during high-temperature sintering. This has been confirmed by microscopic analyses conducted on both the lunar soil simulant and fabricated bricks using scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), and X-ray diffraction (XRD). The mechanical behaviors and failure modes of as-printed and sintered bricks are evaluated, showing compressive strengths of 5-6 MPa and 5-27 MPa, respectively. The elastic modulus and compressive strength of sintered bricks are positively correlated to their relative densities. In addition, bricks featuring mortise and tenon joint structures are also successfully manufactured, enabling direct jointing of different bricks without any binding material, which provides a novel approach to constructing lunar structural components.